Evaluation of EU cooperation with the Caribbean region : final report. Vol. 1 (Commission of the European Union BrusselsBE, 2012)
Presents the findings of the 2011 Regional Level Evaluation of the Commission of the European Union's cooperation with the Caribbean Region. Covers the Regional Strategy Papers for the ninth European Development Fund (EDF9, 2003 - 2007) and (EDF10 - 2008 - 2013), also taking into consideration activities during the evaluation period that had been financed with resources from EDF. Focuses on regional economic and political integration along with private sector development, human resources development, natural disaster prevention and mitigation, and reduction of drug related crime.
Documentation Centre has: 1 CD-Rom which includes Vol. 1: Main report. - Vol. 2: Annexes.